The Use of Competency Models to Assess Leadership in Nursing - KVAS, Andreja (Iran J Public Health, 2013)
BACKGROUND: The efficiency of the health care system is significantly dependent on the appropriate leadership and guidance of employees. One of the most frequently used new approaches in human resources management is the study of competencies and competency models. The aim of this research is to develop a competency model for leaders in nursing, and to compare it with the leadership competency model for state administration. METHODS: A survey was conducted among 141 nurse leaders in Slovenia. The respondents were asked to complete questionnaire with 95 leadership behaviours that form the leadership competency model for leaders in nursing. The data were analysed by ANOVA and Tukey’s honestly significant differences test. RESULTS: The levels of competencies set for themselves by leaders at the third leadership level in nursing (leaders of small units and teams) are significantly lower than those set by all other leaders, both in nursing and in state administration. Statistically significant differences were apparent in the majority of areas. CONCLUSION: Within the context of the comparison of competency models, the greatest need for training can be observed at the third level of leadership in nursing. A comparison of models formulated in this way enables the exchange of good practices among leaders from various professional groups and easier identification of the training needs of individual groups of leaders in public administration. The proposed concept is designed to significantly simplify and unify the building of competency-based leadership models in public sector.